Limonium failachicum (Plumbaginaceae) ― new and so far the only endemic plant from Kuwait - Mucina, Ladislav; Erben, M. (2006)
Limonium failachicum, a new diploid (2n=18) species of Plumbaginaceae, is described from Arabia. The species is taxonomically related to L. iranicum and L. carnosum. The new taxon is so far the only known endemic species for the State of Kuwait. Ecology and distribution of the new species is briefly discussed.